Innovative resources of civic-patriotic education in a preschool educational organization: museum and pedagogical aspect - Polezhaev D. V., Sergeeva E. N. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
the article outlines promising directions for civic-patriotic education of preschoolers during the implementation of a program of innovative activities of a preschool educational organization through museum pedagogy and museological work.
Keywords: патриотическое воспитание; дошкольное образование; педагогические инновации; preschool education; patriotic education; музейная педагогика; museum pedagogy; общероссийская гражданская идентичность; all-Russian civic identity; pedagogical innovations